THE EFFECT OF HUMAN RESOURCE DEVELOPMENT ON EMPLOYEE PERFORMANCE AT THE OFFICE OF THE FINANCIAL AND BLOOD ASSET MANAGEMENT REVENUE AGENCY (BPPKAD) SAMPANG REGENCY - Nasim nasim; Muhammad Alkirom Wildan; Iwanussoleh Iwanussoleh (JPIM (Jurnal Penelitian Ilmu Manajemen), 2024)
ABSTRACT This study aims to analyze the influence of human resource development on employee performance at the office of the Regional Financial and Asset Management Revenue Agency (BPPKAD) of Sampang Regency. Human resource development is one of the important factors that can improve employee performance in an organization. The research method used is a quantitative method with a survey approach. Data was obtained through a questionnaire distributed to BPPKAD employees. The population of this study is all employees at BPPKAD Sampang Regency, with a sample of 96 people. Data analysis uses a multiple linear regression test with an absolute difference test, and a hypothesis test is carried out with a t-test. The results of the study show that human resource development has a positive and significant effect on employee performance. Thus, an effective human resource development program can be a solution in improving employee performance in the agency. Keywords: Human resource development, employee performance, BPPKAD, Sampang Regency